Behavior Management Against the Story of Doctor Jivaka at Lampung Buddhist Sunday School - I Ketut Damana (Institute of Computer Science (IOCS), 2022)
The management's aim is to coordinate general health with the behavior of the traditional Jiwaka healer. Its existence stems from the problem of the lack of access to public services. The importance of flexibility in managing Buddhist behavior management. The research subjects were Sunday school administrators and the objects were Sunday school students. So the implementation model of the approach of the Jiwaka healer's story strategy is realized in the form of support for conscious behavior patterns from administrators, school principals and teachers. The data on the implementation of Sunday Schools is getting more and more trusted, so it is necessary to encourage behavior to maintain health from Sunday Schools. Data collection techniques were carried out through observation, interviews, and documentation. The theory used to analyze the data refers to the concept of Miles and Hubermen, namely collecting data, reducing data, presenting data, and drawing conclusions. The researcher's findings on the input, output and usefulness of managing the process of the omicron impact.